One-step analysis of growth kinetics of mesophilic Bacillus cereus in liquid egg yolk during treatment with phospholipase A2: Model development and validation - Ahmad, Nurul Hawa; Huang, Lihan; Juneja, Vijay (Elsevier, 2024)
Liquid egg yolk (LEY) is often treated with phospholipase A2 (PLA2) to improve its emulsifying capacity and thermal stability. However, this process may allow certain pathogens to grow. The objective of this study was to evaluate the growth kinetics of mesophilic Bacillus cereus in LEY during PLA2 treatment. Samples, inoculated with B. cereus vegetative cells, were incubated isothermally at different temperatures between 9 and 50 °C to observe the bacterial growth and survival. Under the observation conditions, bacterial growth occurred between 15 and 48 °C, but not at 9 and 50 °C. The growth curves were analyzed using the USDA IPMP-Global Fit, with the no-lag phase model as the primary model in combination with either the cardinal temperatures model (CTM) or the Huang square-root model (HSRM) as the secondary model. While similar maximum growth temperatures (Tmax) were determined (48.4 °C for HSRM and 48.1 °C for CTM), the minimum growth temperature (Tmin) of the HSRM more accurately described the lower limit (9.26 °C), in contrast to 6.51 °C for CTM, suggesting that the combination of the no-lag phase model and HSRM was more suitable to describe the growth of mesophilic B. cereus in LEY. The root mean square error (RMSE) of model validation and development was <0.5 log CFU/g, indicating the combination of the no-lag phase model and HSRM could predict the growth of mesophilic B. cereus in LEY during PLA2 treatment. The results of this study may allow the food industry to choose a suitable temperature for PLA2 treatment of LEY to prevent the growth of mesophilic B. cereus. Published by Elsevier Ltd.